2015
DOI: 10.1371/journal.pone.0143419
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Gustatory Cortex Lesions Significantly Impair Taste Sensitivity to KCl and Quinine but Not to Sucrose in Rats

Abstract: Recently, we reported that large bilateral gustatory cortex (GC) lesions significantly impair taste sensitivity to salts in rats. Here we extended the tastants examined to include sucrose and quinine in rats with ibotenic acid-induced lesions in GC (GCX) and in sham-operated controls (SHAM). Presurgically, immediately after drinking NaCl, rats received a LiCl or saline injection (i.p.), but postsurgical tests indicated a weak conditioned taste aversion (CTA) even in controls. The rats were then trained and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 64 publications
4
28
0
Order By: Relevance
“…However, damage to those higher structures would produce loss of hierarchical control but not loss of original functions remaining in lower structures. These considerations may help explain why cortical lesions of the hedonic hotspot/coldspot sites identified here have generally failed to impair measures of food reward (12,14,61,64). Similarly, human patients with extensive damage to OFC and insula appear to remain capable of normal hedonic reactions to many pleasant versus unpleasant stimuli (9,10).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, damage to those higher structures would produce loss of hierarchical control but not loss of original functions remaining in lower structures. These considerations may help explain why cortical lesions of the hedonic hotspot/coldspot sites identified here have generally failed to impair measures of food reward (12,14,61,64). Similarly, human patients with extensive damage to OFC and insula appear to remain capable of normal hedonic reactions to many pleasant versus unpleasant stimuli (9,10).…”
Section: Discussionmentioning
confidence: 71%
“…However, the role of the cortex as necessary for "liking" is questioned by evidence that cortical damage usually does not cause loss of hedonic function: Lesions in the OFC, insula, or anterior cingulate cortex in humans do not reliably suppress positive hedonic reactions to many pleasant stimuli, despite causing cognitive impairments that alter decisions about selection, pursuit, and consumption of rewards (7)(8)(9)(10)(11). Similarly in animal studies, cortical lesions fail to strongly suppress reward-elicited behaviors (12)(13)(14).Showing that the cortex causes gains of function in the motivation to consume food rewards, Mena et al (15) recently reported that cortical mu-opioid stimulation in rats, via microinjections of DAMGO, a synthetic opioid agonist with high mu-opioid receptor selectivity, in the medial prefrontal cortex (PFC) produced robust increases of food intake. Here, we aimed to assess whether similar opioid stimulations in the prefrontal and insula cortex might also specifically cause increases in the hedonic impact of the sensory pleasure of food, as assessed by orofacial "liking" reactions to sweetness.Beyond opioid stimulation, orexin stimulation has been found to similarly cause "liking" enhancements in the same NAc and VP hotspots where DAMGO enhances hedonic impact (16, 17), raising the possibility that any cortical opioid hotspot for "liking" enhancement might also be stimulated by orexin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The same lesions retarded the acquisition of a NaCl versus KCl discrimination, even though it was eventually learned (Blonde, Bales, & Spector, 2015). Bales, Schier, Blonde, and Spector (2015) replicated the impairment in KCl detection in rats with large bilateral lesions in GC (~91% damage) and these same rats also displayed a modest rightward shift in sensitivity to quinine, but, surprisingly, they displayed absolutely no impairment in the detection of sucrose.…”
Section: Introductionmentioning
confidence: 81%
“…Anatomical landmarks distinctly associated with one brain section, according to the rat brain atlas (Paxinos & Watson, 2007), were used to determine the best approximate AP coordinate (see Bales et al, 2015; Table 2). The AP distance between the landmarks as seen in the atlas was divided by the number of sections between those landmarks for each brain.…”
Section: Methodsmentioning
confidence: 99%